Potency of Soybean Development in Peat land District of Kubu Raya West Kalimantan - Dina Omayani Dewi (Fakultas Pertanian, Universitas Janabadra, 2017)
Agricultural development is very important as a motor of national economy. Local resources need to be empowered to improve the welfare of farmers' communities. The empowerment provides the impact of problems and opportunities in the development of soybeans in West Kalimantan. Ministry of Agriculture of the Republic of Indonesia has made West Kalimantan Province as one of the priority of agroindustry development of beans and tubers. The development of nuts, such as soybeans, is part of food diversification efforts. This research was conducted from June to October 2016 in Kabupaten Kubu Raya, West Kalimantan. The results showed that Kabupaten Kubu Raya has potential for soybean development. This is supported by natural resources, land resources, and farm resources. The result of marketing analysis shows that R / C ratio for soybean is about 2.03 with net income that can be accepted by farmers around IDR 13.270.000 per year.